RenderAnts: Interactive Reyes Rendering on GPUs - Zhou, Kun; Hou, Qiming; Ren, Zhong; Gong, Minmin; Sun, Xin; Guo, Baining (ACM Transactions on Graphics, 2009)
We present RenderAnts, the first system that enables interactive REYES rendering on GPUs. Taking RenderMan scenes and shaders as input, our system first compiles RenderMan shaders to GPU shaders. Then all stages of the basic REYES pipeline, including bounding/splitting, dicing, shading, sampling, compositing and filtering, are executed on GPUs using carefully designed dataparallel algorithms. Advanced effects such as shadows, motion blur and depth-of-field can be also rendered with our system. In order to avoid exhausting GPU memory, we introduce a novel dynamic scheduling algorithm to bound the memory consumption during rendering. The algorithm automatically adjusts the amount of data being processed in parallel at each stage so that all data can be maintained in the available GPU memory. This allows our system to maximize the parallelism in all individual stages of the pipeline and achieve superior performance. We also propose a multi-GPU scheduling technique based on work stealing so that the system can support scalable rendering on multiple GPUs. The scheduler is designed to minimize inter-GPU communication and balance workloads among GPUs. We demonstrate the potential of RenderAnts using several complex RenderMan scenes and an open source movie entitled Elephants Dream. Compared to Pixar’s PRMan, our system can generate images of comparably high quality, but is over one order of magnitude faster. For moderately complex scenes, the system allows the user to change the viewpoint, lights and materials while producing photorealistic results at interactive speed.
to appear